VDC_100102371237.0X000001. Issue 10 (October 2018) - Al-Temimi, Mohammed H.; Trujillo, Charles; Shah, Mital; Rangarajan, Sriram; Kim, Edwin; Chandrasekaran, Bindupryia; Handman, David; Johna, Samir
Same-day endoscopic retrograde cholangiopancreatography (ERCP) and cholecystectomy (LC) could potentially reduce hospital length of stay (HLOS). Patients undergoing same-day procedures (N = 164) between 2012 and 2014 were compared with different-day procedures performed in the second half of 2014 (N = 276), in the Kaiser Permanente Southern California database. Both groups had comparable baseline characteristics. ERCP success rate (97.5% vs 93.5%), overall postoperative morbidity (3.66% vs 3.99%), and retained stones (2.5% vs 5.8%) were not different between groups ( P > 0.05); however, HLOS was shorter in the same-day group (2.99 ± 2.34 vs 3.84 ± 2.52 days, P < 0.001). Morbidity, procedure success, and HLOS were not different in the same-day group, whether ERCP was performed before or after LC ( P > 0.05). In the same-day group, those undergoing single anesthesia had higher BMI (40.1 ± 10.8 vs 30.3 ± 6.6) and were more likely to have gastric bypass (30% vs 0%) than those undergoing separate anesthesia sessions ( P < 0.01). Longer HLOS (4.8 ± 3.5 vs 2.9 ± 2.2 days) and higher estimated blood loss (65 ± 90 mL vs 20 ± 29 mL) were also associated with the single-anesthetic session ( P < 0.01). ERCP performed on the same day of LC reduces HLOS without increasing morbidity. This approach does not affect postoperative morbidity and ERCP success rate, whether ERCP was performed before or after LC.